Development of a Transport Module for Multi-topic Household Surveys - Baker, Judy L.; Denning, William (World Bank, Washington, DC, 2014)
This paper is aimed at providing guidance on transport issues for those involved in designing multi-topic household surveys such as the Living Standards Measurement Studies (LSMS) surveys. The inclusion of a few key questions can provide critical information for better designing transport programs and policies aimed at improving access, affordability and quality services. Questions on transport access, quality, mode, distance, time, and cost can help to understand the constraints that the population may face in accessing jobs, markets, schools, health clinics and other social services. All of this can be broken down by subgroups such as income, geographic area, gender, employment, etc. further strengthening the relevance of the analysis and contribution to policy decisions. The paper covers background on transport and multi-topic household surveys, key transport policy concerns and data needs, approaches to analysis, issues of survey design, and prototype questions that could be included in existing surveys.